Scapular-muscle performance: Two training programs in adolescent swimmers - van de Velde, A.; de Mey, K.; Maenhout, A.; Calders, P.; Cools, A. M. (Journal of Athletic Training, 2011)
Context: Swimming requires well-balanced scapular-muscle performance. An additional strength-training program for the shoulders is pursued by swimmers, but whether these muscle-training programs need to be generic or specific for endurance or strength is unknown.